Security Sector Transformation in Southeastern Europe and the Middle East - Dokos, Thanos (IOS Press, 2013)
For most countries, security today is primarily measured in non-military terms and threats to security are non-military in nature. These threats include incompetent government, corruption, organized crime, insecure borders, smuggling [weapons, drugs, contraband, people], illegal migration, ethnic and religious conflict, proliferation of weapons of mass destruction, shortage of natural resources [e.g., water] and, of course, terrorism